GIMNASTIC JUMPS - OVER AND THEIR CONNECTION WITH MOTORIC ABILITIES OF THE FIFTH GRADE STUDENTS - Radojica Marušić; Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
This resurch is undertaken for the purpuse of defining and determinating of the total degree of connection between some motoric skills with efficiency in realization of some programme issnes in the area of gymnastic (stretched - legged jump and folded - legged jump). On the sample of fifty one student from the fifth grade of Elementary School, examined students have been tested on ten motoric tests and on two specific motoric assignments: streched - legged jump and foled - legged jump. The results show that there are many statisticaly important coefficients of correlation between motoric skills tested and motoric assignments applied